Pengaruh Motivasi, Kompetensi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Sindo Megah Lestari - Erna Noferianti; Wasiman Wasiman (Komunitas Dosen Indonesia, 2022)
Human Resources are an important component in deciding whether an association is healthy. Increasing human resources that are organized and insightful is an absolute necessity, especially for the fate of the community. In these ecological conditions, executives are needed to push for better approaches to keep workers highly usable and grow their potential to provide top-level input to associations. HR problems which are actually only internal problems of an organization do have a close relationship with the wider area as public assistance as predicted by execution workers. That studies aims to determined the effects of motivations, competences, and work environments on employee performances at PT Sindo Megah Lestari. That researches designed using researches design and quantitative research methods. The result of this studies indicated that motivation (X1), competence (X2), and work environment (X3) partially and simultaneously have a significants effects on employee performance (Y). The result of the coefficient of determinations test showed that motivation (X1), competence (X2), and work environment (X3) partially and simultaneously have a significants effects on employee performance (Y) by 61 percents, while the rest is influence by other variable not examine in that study.